Jember Fashion Carnival (JFC) as a National Culture Viewed from Islamic Law Perspective - Yaqin, Husnul; Ira Eka Pratiwi; Taufiqur Rohman; Balkis Nur Azizah (Hikmatuna : Journal for Integrative Islamic Studies, 2021)
The purposes of this research were to (1) describe the practice of the Jember Fashion Carnival (JFC), which is held in Jember, Indonesia, and (2) explain how the practice of the Jember Fashion Carnival (JFC) is regarded from the perspective of Islamic law. This research is included in the qualitative-descriptive and literature research category. In conclusion, (1) the Jember Fashion Carnival (JFC) is a cultural event as well as a carnival that is held every year with a specific theme; this spectacular activity attracts foreign tourists and helps to boost the economy, among other things; and (2) the entire event contained in the Jember Fashion Carnival (JFC) is a good culture that does not conflict with Islamic law. As a result, it is feasible and may be implemented as a normal culture within the local community. No action taken at the Jember Fashion Carnival (JFC) activity violates Islam, nor does it ban something permissible, nor does it cancelsomething compulsory, invalidate the meaning of benefit, nor does it foster the growth of evil.